Bot Chat : Customer Relation dengan Teknologi Artificial Intelligence - Laksana Utama, Putu Kussa (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
The application of Artificial Intelligence (AI) is increasingly massive in the industries. One of the advantages of implementing AI is operational efficiency, because by using AI that is implemented on computer machines, the use of human as an operator in an industry can be minimized. This certainly affects the operational efficiency of an organization. One form of AI implementation in the industries is the Chatbot program. Chatbot is a virtual program that is able to communicate like a human. In many cases, Chatbot take role in the Front-End section of an organization that functions as a customer relations medium. This paper aims to examine various techniques of developing Chatbot for the past 8 years in the academic research environment. In this paper there are 6 scientific articles reviewed focusing on the their techniques and methods of development. The results obtained show that there has been a shift or development of Chatbot's communication features, from the original symbol-based computer keyboard to audio-based speech recognition. Also, there are variations in the construction of knowledge bases, ranging from AIML to semantic based.